Science by social media: Attitudes towards climate change are mediated by perceived social consensus - Lewandowsky, Stephan; Cook, John; Fay, Nicolas; Gignac, Gilles E. (Memory & cognition, 2019)
Internet blogs have become an important platform for the discussion of many scientific issues, including climate change. Blogs, and in particular the comment sections of blogs, also play a major role in the dissemination of contrarian positions that question mainstream climate science. The effect of this content on people’s attitudes is not fully understood. In particular, it is unknown how the interaction between the content of blog posts and blog comments affects readers’ attitudes. We report an experiment that orthogonally varied those two variables using blog posts and comments that either did, or did not, support the scientific consensus on climate change. We find that beliefs are partially shaped by readers’ perception of how widely an opinion expressed in a blog post appears to be shared by other readers. The perceived social consensus among readers, in turn, is determined by whether blog comments endorse or reject the contents of a post. When comments reject the content, perceived reader consensus is lower than when comments endorse the content. The results underscore the importance of perceived social consensus on opinion formation.